Hubungan Kinerja terhadap Kesejahteraan Guru SMA Se Makassar - subair, ahmad (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Welfare teachers have an important role in determining their performance in the educational environment, especially in improving the effectiveness of teaching and student management. This research aims to analyze the relationship between teacher welfare, which includes economic, social and psychological welfare, and the performance of high school teachers in Makassar City. This research uses quantitative methods with a correlational descriptive design. Data was collected through a survey with a closed questionnaire from 150 teachers randomly selected from 10 high schools in Makassar City. The research results show that there is a significant positive relationship between teacher well-being and their performance, especially in the dimension of psychological well-being which has the greatest influence on performance. The correlation between economic and social well-being and performance is also significant, although there is no relationship between well-being and psychological well-being. These findings indicate the importance of paying more attention to teachers' rewards, social support, and psychological conditions, in addition to financial aspects, to improve the quality of their performance in the educational environment. This research recommends the need for a comprehensive policy to improve teacher welfare to support optimal performance in schools.